Entrepreneurship : Creative Partners / Nor Shafazillah Al Munnawarah Shafie, Amy Nursyuhada Mazlan and Nik Aznida Nik Abu Bakar - Shafie, Nor Shafazillah Al Munnawarah; Mazlan, Amy Nursyuhada; Nik Abu Bakar, Nik Aznida (2009)
CREATIVE PARTNERS is a firm that expel a product in term of direct advertising to customer that come from any agencies or organizations that want to advertise their product or to inform any information 'to other people. In short, we offer printing services. Our firm product comes from plastic material that has a higher quality (Taipaulin). This product actually change the old product (felted material) because the felted material easy to soiled and its color easy to dim.